2021
DOI: 10.21203/rs.3.rs-253600/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Establishment of sex difference in circulating uric acid is associated with higher testosterone and lower sex hormone-binding globulin in adolescent boys

Abstract: Men have higher circulating levels of uric acid than women. This sex difference is suspected to be a result of suppressive effects of estradiol on uric acid. If so, estradiol would be inversely associated with circulating uric acid. This study aimed to test this hypothesis. This cross-sectional study included 9 472 participants (weighted sample size of 184 342 210) aged 12–80 years from the 2013 to 2016 US National Health and Nutrition Examination Survey. Associations of sex hormones with uric acid were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Our study also indicates that testosterone could promote higher levels of kidney function markers ( i.e ., creatinine and uric acid) since subjects with basal and restored testosterone levels showed an increased abundance of these metabolites (Table 2 and Figure 4D). These findings are in agreement with a recent study where higher testosterone was associated with an increment in uric acid levels in adolescent boys 33 , and a case report of hypogonadism where renal function decreased after testosterone replacement therapy, increasing creatinine levels 34 . However, considering that creatinine is also involved in muscle metabolism, the positive correlation between testosterone and creatinine might reflect the increase in muscle mass and not an impairment in renal function 35 .…”
Section: Discussionsupporting
confidence: 93%
“…Our study also indicates that testosterone could promote higher levels of kidney function markers ( i.e ., creatinine and uric acid) since subjects with basal and restored testosterone levels showed an increased abundance of these metabolites (Table 2 and Figure 4D). These findings are in agreement with a recent study where higher testosterone was associated with an increment in uric acid levels in adolescent boys 33 , and a case report of hypogonadism where renal function decreased after testosterone replacement therapy, increasing creatinine levels 34 . However, considering that creatinine is also involved in muscle metabolism, the positive correlation between testosterone and creatinine might reflect the increase in muscle mass and not an impairment in renal function 35 .…”
Section: Discussionsupporting
confidence: 93%
“…Confounding covariates were similar to the previous publications 11–13,17,18 and included age (continuous), sex (male or female), ethnicity (Non‐Hispanic White, Non‐Hispanic Black, Mexican‐American, or other), obesity (underweight, normal, overweight, obese, or unknown), poverty‐income ratio (<130%, 130%–349%, ≥350%, or unknown), education (<high school, high school, >high school, or unknown), and survey periods (1988–1991, 1991–1994, 1999–2000, 2001–2002, 2003–2004, 2005–2006, 2007–2008, 2009–2010, 2011–2012, or 2013–2014). Lifestyle confounders included physical activity (inactive, insufficiently active, active, or unknown), alcohol consumption (never, <1 drink per week, 1–6 drinks per week, ≥7 drinks per week, or unknown), and smoking status (past smoker, current smoker, nonsmoker, or unknown).…”
Section: Methodsmentioning
confidence: 99%
“…It was observed that there was a different relationship between sUA and HNT in people of different genders [19]. Previous studies [21] have shown that Figure 3: Association between sUA and HTN stratified by sex. Age, race, income-poverty ratio, physical activity, smoking behavior, alcohol consumption, diabetes mellitus status, body mass index, total cholesterol, serum homocysteine, urine creatinine, blood urea nitrogen, and total calcium were adjusted.…”
mentioning
confidence: 86%